At the Frontlines of Development : Reflections from the World Bank - Gill, Indermit S.; Pugatch, Todd (Washington, DC: World Bank, 2012)
At the Frontlines of Development former World Bank country directors recount their experiences, both as managers of the World Bank's programs in global economic hotspots of the 1990s as well as throughout their careers in development economics. These essays detail, among many stories of development in the 1990s, how China and India lifted hundreds of millions out of poverty, while Russia collapsed; how Bosnia and Herzegovina and Mozambique remade their war-ravaged economies; and how Thailand, Turkey, and Argentina fell into financial crisis. These remarkable stories, told in first-person by the country directors who were there to witness them, provide candid assessments of development in the 1990s-what succeeded, what failed, and what lessons emerged.